Charles D. Brower diary - Brower, Charles D., 1863-1945.
Diary (64 pages).
Handwritten and typewritten transcript.
Trader and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Authors; Traders